Deformation induced hardening when cryogenic turning,. (November 2018) - Mayer, Patrick; Kirsch, Benjamin; Müller, Christopher; Hotz, Hendrik; Müller, Ralf; Becker, Steven; von Harbou, Erik; Skorupski, Robert; Boemke, Annika; Smaga, Marek; Eifler, Dietmar; Beck, Tilmann; et al.
Abstract: In recent years, deformation induced surface hardening when turning was carried out to enhance the component performance of metastable austenitic steels. To induce such a phase transformation from austenite to martensite in the workpiece surface layer, high mechanical loads and low process temperatures are required. Therefore, cryogenic CO2 -snow cooling is an appropriate method to assure low temperatures in the workpiece surface layer. In this context, the influence of the process parameters cutting speed, feed, depth of cut and tool cutting edge inclination on the surface morphology in terms of deformation induced surface hardening and resulting surface roughness was investigated. The results show that the deformation induced surface hardening when cryogenic turning is adjustable via a targeted variation of the investigated process parameters. Thus, the morphology of the surface layer and therefore the properties of the component can be adjusted according to the requirements of the application.